IMPLEMENTATION OF MULTICULTURAL-BASED LEARNING AT SMA NEGERI 8 KUPANG - Poas Mangmani (SocioEdu: Sociological Education, 2022)
This study aims to determine the implementation of multicultural-based learning at SMA Negeri 8 Kupang. The subject of this study were students, teachers, and vice principals. The data were obtained through observation, interview, and documentation. The study showed that multicultural-based learning was not included in the school curriculum, but the teacher was able to apply it in the teaching and learning process. Hence, the implementation of multicultural-based learning at school had been integrated with the subject materials in the curriculum. The goal is that the students can appreciate, and respect all the differences and make these differences in their citizenship statuses. Besides, it also become the hallmark of the nation and state life. The implementation of multicultural education was carried out through three programs, namely, a material-oriented program, a student-oriented program, and a social-oriented program.